(3OjhGf GdZRjs - (3GdZRj , EHQGgje Hf YKeGf Hf eMeO GdcdHj GdGTgHj, CHh ESMGb CHh YKeGf,J (B524 (3g` s ((3HZOGO s)
(3ChdgG (B:s
(3MQa GdgeRI(B: (3bGd GdTjN CHhGSMGb jeOM GdhRjQ eYjf GdOjf GdeNJU(B: (3UHGM fhGce dG CUd eSGA hgOe ghGce HGdedGe HfGA s
(3BNQgG (B:s
(3MQa GdgGA hbGd aj GdTjNhNI(B: (3Whd MjGI eGdgG fZU YfOj cd eG ojTJgi hgPG eG hLO aj eShOGJg, CeG HGbjgG aGfJMdgG UGMH dg s
(3fSNI KGdKI Yf fSNI cKjQI GdJUMja hGdJMQja ocJHJ SfI (B964(3g```s
(3hgh eQJH Ydi GdMQhas
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B44s
Keywords: (3GdCOHs